Have US Workers’ Job Security Perceptions Decreased Since the 1990 Recession ? - Leduc, Sébastien (Université d'Ottawa | University of Ottawa, 2009)
In this paper, I verify whether American workers changed their perceptions regarding job security the 1990 recession. Using Data from the General Social Survey from 1977 to 2006, and based on three different measures of perceived insecurity. I find that i